Conventional and inverse elastocaloric effect in Ni-Fe-Ga and Ni-Mn-Sn ribbons. (February 2017) - Álvarez-Alonso, P.; Aguilar-Ortiz, C.O.; Villa, E.; Nespoli, A.; Flores-Zúñiga, H.; Chernenko, V.A.
Abstract: Magnetic shape memory Ni55 Fe16 Ga29 and Ni50 Mn40 Sn10 melt spun ribbons have been characterized by thermomechanical and mechanical analysis. Martensitic transformation temperatures show an abnormal tendency to decline under low stress followed by a conventional increase above a threshold stress, related to the internal compressive stress generated in the fabrication process. The shrinkage of the samples during the forward martensitic transformation gives rise to an inverse elastocaloric effect. A conventional contribution in the total elastocaloric response is observed when applied stress overcomes the internal one. The conventional and inverse elastocaloric effects are attributed to the stress-induced forward and reverse martensitic transformation, respectively. Graphical abstract: